Disease activity score in 28 joints at 3 months after the initiation of biologic agent can be a predictive target for switching to the second biologic agent in patients with polyarticular juvenile idiopathic arthritis. Issue 3 (3rd May 2016) - Kubota, Tomohiro; Imanaka, Hiroyuki; Takei, Syuji; Yamatou, Tsuyoshi; Nerome, Yasuhito; Yamasaki, Yuuichi; Nonaka, Yukiko; Akaike, Harumi; Takezaki, Tomoko; Kawano, Yosihumi
Abstract: Objective : To clarify polyarticular juvenile idiopathic arthritis (pJIA) patients who failed to maintain prolonged remission with the first biologic agent. Methods : Fourteen pJIA patients were observed for 47.5 months (median) after initiating the first biologic agent. Results : Eight maintained sustained clinical remission (median 47 months) with the first biologic agents, while the six switched to the second one due to lack of efficacy, thereafter. Receiver operating characteristic (ROC) analysis revealed that disease activity score in 28 joints (DAS28) of 2.37 at 3 months could distinguish between the two patient groups ( p  = 0.001). Conclusion : pJIA patients with DAS28 >2.37 at 3 months of the initial biologic therapy may be considered to switch to the second biologics.